Perbedaan Kualitas Kehidupan Kerja Pada Dosen Tetap PNS (DTPNS) Dan Dosen Tetap Non PNS (DTNPNS) Di UIN Raden Fatah Palembang - Dwi Despiana (Jurnal Ilmiah Psyche, 2023)
Quality of work life is a concept of how to appreciate the competence and performance of employees in the organization. The quality of work life is very important in increasing the contribution of employees to the organization. This study aims to determine the differences in the quality of work life between DTPNS and DTNPNS at UIN Raden Fatah Palembang. The quality of work life has an important role for lecturers in carrying out the duties of the Tri Dharma of Higher Education. The subjects of this study were 90 people. Sampling research using accidental sampling technique. The data collection method uses a quality of work life scale (Swamy, et al, 2015) with aspects of quality of work life, namely: (1) work environment; (2) organizational culture and climate; (3) relations and co-operation; (4) training and development; (5) compensation and rewards; (6) facilities; (7) job satisfaction and job security; (8) autonomy of work; (9) adequacy of resources. Based on the results of hypothesis testing using the independent sample t-test, the average variance for PNS lecturers (DTPNS) is greater than the average variance for non PNS lecturers (DTNPNS), namely 180.11 > 157.71 with a significance of 0.000 (p <0.05), so it shows that there is a difference in the quality of work life for DTPNS and DTNPNS at UIN Raden Fatah Palembang.